1974
DOI: 10.1111/j.1476-5381.1974.tb09625.x
|View full text |Cite
|
Sign up to set email alerts
|

The HAEMODYNAMIC EFFECTS OF PROLONGED ORAL ADMINISTRATION OF OXYFEDRINE, a PARTIAL AGONIST AT Β‐ADRENOCEPTORS: COMPARISON WITH PROPRANOLOL

Abstract: 1Haemodynamic changes have been studied in cats after the chronic oral administration of oxyfedrine (14 mg/kg for 3-4 weeks) or of placebo (lactose). The initial part of the study was carried out under double-blind conditions. The arterial blood pressure was between 19 mmHg (diastolic) and 27 mmHg (systolic) higher in the oxyfedrine treated animals, but there were no differences between the two groups with regard to cardiac output, left ventricular dP/dt max, heart rate or systolic ejection time. 2 In cats sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1974
1974
1991
1991

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…*P < 0.0005; **P < 0.005; ***P < 0.025. Parratt, 1973;1974). Endotoxin administration resulted in a substantial metabolic acidosis ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…*P < 0.0005; **P < 0.005; ***P < 0.025. Parratt, 1973;1974). Endotoxin administration resulted in a substantial metabolic acidosis ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Another intriguing question which requires answering is whether, following prolonged administration of oxyfedrine to anginal patients, it loses its agonist properties whilst retaining its antagonist properties at f3-adrenoceptor sites. In a relevant animal study, although admittedly with much larger doses than those used by the Northwich Park group, one of us (Parratt, 1974) found that isoprenaline dose-responses curves were shifted to the right following oral treatment with oxyfedrine for 3-4 weeks (evidence of f8-adrenoceptor blockade) yet there was no reduction in resting cardiac output, left Br. J. clin.…”
Section: Possible Mechanisms Of Action Of Oxyfedrine As An Antianginamentioning
confidence: 99%
“…Four of these variables were also displayed continuously on an oscilloscope (Racal Instruments type 9383). Cardiac output was measured by thermodilution (using simple copper-constantan thermocouples; Parratt, 1974) and the heart rate was measured from the electrocardiogram. Body temperature was recorded from the rectum and mid-oesophagus with direct recording thermocouples (Ellab, Copenhagen).…”
Section: Methodsmentioning
confidence: 99%
“…Body temperature was recorded from the rectum and mid-oesophagus with direct recording thermocouples (Ellab, Copenhagen). Blood gases, pH and arterial lactate were measured by methods previously described in full (Parratt, 1974 pJkg. The effects of D4975 were also examined before, and 10 to 30 min after the intravenous administration of propranolol (0.25 mg/kg).…”
Section: Methodsmentioning
confidence: 99%